2022
DOI: 10.3390/microorganisms10030583
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting and Molecular Identification of Used Transformer Oil-Degrading Bacteria for Bioplastics Production

Abstract: One of the major impediments to the commercialization of biodegradable plastic is the high cost of substrate. Consequently, there is a continuous search for effective microorganisms and cheaper carbon substrates to reduce the high production cost. In this study, waste transformer oil-degrading bacteria were isolated from soil, wastewater, and sediment samples, using a mineral salt medium (MSM) supplemented with 1% waste transformer oil as the sole carbon source. The isolates were screened for polyhydroxyalkano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Furthermore, the data obtained from the GC-MS and NMR analyses of the synthesised polymer revealed that the PHA might have been composed of 3HHD and 3HOD as the major monomer constituents. This is comparable with a similar finding extensively described elsewhere [ 32 ]. In Table 6 , the molecular weight and thermal properties of the polymer produced by Acinetobacter sp.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, the data obtained from the GC-MS and NMR analyses of the synthesised polymer revealed that the PHA might have been composed of 3HHD and 3HOD as the major monomer constituents. This is comparable with a similar finding extensively described elsewhere [ 32 ]. In Table 6 , the molecular weight and thermal properties of the polymer produced by Acinetobacter sp.…”
Section: Discussionsupporting
confidence: 93%
“…This isolate was found to be a Gram-negative coccobacillus and designated as Acinetobacter sp. strain AAAID-1.5 with gene accession number MZ411700 [ 32 ]. The organism was used in the PHA production in shake flasks via a batch process biosynthesis with UTO as the sole carbon source.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular detection and subsequent phenotypic verification of the production of PHA can lead to the understanding of the biosynthetic pathways and thus to the prediction of the appropriate substrate and the resulting type of PHA formed. As a result, new producing strains may be discovered presenting a cheaper and more available substrate, leading to lower production costs of PHAs [ 10 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The production of P(3HB) homopolymer by Bacillus thuringiensis and Bacillus cereus from glucose was demonstrated in a study by Ray and Kalia [ 35 ]. The ability to use inexpensive substrates from waste transformer oil, waste-derived volatile fatty acids, and other types of waste were reported [ 30 , 36 ]. Priestia megaterium was identified among the isolates which produced PHA from sugars and propionic acid.…”
Section: Discussionmentioning
confidence: 99%